Aerodynamics Analysis of Mobil Irit Tarumanagara using CFD Method. Issue 1 (December 2020) - Kesuma, Poppy; Darmawan, Steven; Halim, Agus
Abstract: Aerodynamics on vehicles plays an important role in increasing the efficient vehicles. Nowadays, research in the field of aerodynamics of four-wheeled vehicles is carried out with the concept of optimization of the geometry shape of the vehicle. Some studies found that the best form in the aerodynamic aspect is the streamlined form, because it has the lowest resistance coefficient value, which is 0.04. Previously, the body of Mobil Irit Tarumanagara designed conventionally in Eco Vehicle concept, using experiments method. The experiments method is very complicated and inefficient, because engineers must draw the designs first, mock- up making, making negative molds, and then mold-casting. Aside from the processes, the aerodynamics performance of Mobil Irit Tarumanagara need to be analyzed. Therefore, this study will analyze the aerodynamics performance of Mobil Irit Tarumanagara using CFD (Computational Fluid Dynamic). CFD simulation will be done on 3D on 3 different body models and 5 speed variations: 1.39 m/s; 2.78 m/s; 4.17 m/s; 5.56 m/s; and 12.5 m/s. The mesh used is in tetrahedral form with a total of 76752 nodes in body no. 1; 55439 nodes in body no. 2; 42551 nodes in body no. 3. The results of the simulation presented by two flow parameters; velocity and pressure which shows the best body model is body 3, because it has the most aerodynamics performance, especially at the front and back of the body. The air velocity at front reaches 9.387 m/s; and vortices at the back flows in 3.271 m/s. This results serve as a reference for development on Mobil Irit Tarumanagara's body model